Investigation of emotional changes using features of eeg-gamma band and different classifiers [Duygu durum deǧişimlerinin EEG-gama bandi öznitelikleri ve farkli siniflandiricilar ile incelenmesi] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2019)
This study focuses on a signal processing method, which qualifies the relation between the emotional stimulation and emotional changes in healthy participants. For this purpose, an emotional EEG-based database was created by using stimuli which represented to the participants by using Nencki Affective Picture System (NAPS) for the scope of this study. Then, signal processing which includes Power Spectral Density (PSD) and a number of classification analysis is investigated. PSD was analyzed for the emotion connectivity between three types of emotional stimuli to the sub frequency band (gamma band) of the collected EEG-based data. In recent times, most of the studies commonly concentrated on the Brain-Computer Interface (BCI) and we aim that this study performed on emotional changes analyses based BCI systems will be estimable work for the researchers working in this scope. © 2019 IEEE.
Keywords: Classification; EEG; Emotion estimation; Power spectral density